Research-Based Learning (RBL) as a Factor for Strengthening Syllabi of Universidad Quintana Roo en Playa del Carmen, México - Figueroa de la Fuente, Mariana (2018)
This paper analyzes the characteristics of Research-Based Learning (RBL) with the aim of understanding how the articulation of teaching and the research process can be a factor for strengthening higher education, specifically at the University of Quintana Roo, Playa del Carmen Academic Unit (UAPC). To do this, significant documents and literature were revised using qualitative techniques. This phase contributed to the design of a structured questionnaire to carry out a survey which allowed knowing the disposition and the obstacles to implement the RBL at UAPC. Among the findings, the following stand out: the interest of the faculty members to strengthen its investigative capabilities, training in theoretical knowledge about the RBL, and the involvement of students in research in order to be able to cope with the need for creative professionals with a capacity to analyze, to think critically, write and express themselves effectively, solve complex problems, synthesize, among other challenges of the educational reality of the 21st Century.